2020
DOI: 10.1039/d0cp03260c
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast acoustic vibrations of Au–Ag nanoparticles with varying elongated structures

Abstract: Acoustic vibrations of Au and Ag elongated nano-objects with original morphologies, from Ag–Ag homodimers to Au@Ag–Ag heterodimers and Au@Ag eccentric core–shell spheroids, have been experimentally investigated by ultrafast time-resolved optical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…An extensive and detailed review of work in this area was given [79], and a more recent one focused on the measurement techniques [80]. Recent works include the analysis of compound nanoparticles [81], analyses concerning the exploitation of nanoplates as antennas in the conversion from the laser pulse to the acoustic pulse [82], and work in the direction of the imaging of acoustic modes [83].…”
Section: Picosecond Ultrasonicsmentioning
confidence: 99%
“…An extensive and detailed review of work in this area was given [79], and a more recent one focused on the measurement techniques [80]. Recent works include the analysis of compound nanoparticles [81], analyses concerning the exploitation of nanoplates as antennas in the conversion from the laser pulse to the acoustic pulse [82], and work in the direction of the imaging of acoustic modes [83].…”
Section: Picosecond Ultrasonicsmentioning
confidence: 99%
“…This technique, which allows to measure the vibrations on ensemble [15][16][17] but also on a single nanoparticle [18][19][20] have proven to be a very efficient way [21][22][23][24]. Therefore, it has been employed in order to study the shape-, size-, or material-dependence of the vibrational response for a large variety of mNOs [15,18,19,[25][26][27][28][29][30][31][32][33][34][35]. In particular, it has been shown that the environment greatly affects the vibrations of a mNO, notably the damping rate [34,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…The breathing frequency decreases with the addition of silver, whereas the extensional mode is almost unchanged. Related systems based on gold bipyramids [27] or nanosphere dimers [28] have also been prepared and studied.…”
Section: Introductionmentioning
confidence: 99%